A New Method of Extraction and Measurement of Paraquat using BN/SPE Method Using High-Performance Liquid Chromatography - Marzieh Piryaei; Mir Mahdi Abolghasemi; Monireh Sobhi (Nanochemistry Research)
The present study was the first report in the needle-based SPE for quantitative analysis of paraquat herbicide, which is a very sensitive, economical, and small method that can be performed at the laboratory level. Boehmite nanoparticles (BN/SPE) coupled with high-performance liquid chromatography equipped with UV detector was developed for the rapid removal of paraquat herbicide from a natural water sample. Solid phase extraction is a widely employed technique in environmental science for pre-concentration and purification purposes. Nevertheless, conventional methods necessitate the use of electrically powered pumps, large amounts of solvent (especially when multiple samples are processed), and significant time investment to filter a sample. Moreover, if the cartridge is exposed to the atmosphere, there is a risk of volatile compounds being lost and compromising the integrity of the sample. In contrast, needle tip-based solid phase extraction offers several advantages. It can be manually completed in under 2 minutes, requires only microliters of solvent, and yields comparable concentration factors to established methods. Furthermore, it operates as an enclosed system, preventing the loss of volatile components. In this paper, a novel extraction technique termed needle tip-based solid phase nano extraction was developed that describes a rapid method for the quantitative analysis of paraquat from an environmental water sample. Under the optimum extraction conditions, the method showed good linearity in the range of 1–100 µg/mL, acceptable reproducibility (RSD: 0.9507, n =4), and limits of detection (0.1µg/mL).